Interview with John McIntire, editor of the ILRI impact book - McIntire, John M. (International Livestock Research Institute, 2021)
Former ILRI deputy director general for research, John McIntire, is an independent economist who edited the ILRI impact book. Read about ILRI's impact book, covering over 45 years of research at:- ilri.org/ILRI-research-impact